Addressing the ACGME Competency of Communicating with the Public through the Use of TEDx Talks. Issue 12 (December 2022) - Lin, Ashleigh Peng; Liu, Shao-Ying; Chen, Tzu-Tao; Huang, Shin-Yi; Wu, Bei-Wen; Lin, Yen-Kuang; Tam, Ka-Wai
Abstract : Postgraduate year (PGY) trainees were given the opportunity to train and participate as speakers for a technology, entertainment, and design (TED)x event. The efficacy of TED talks in PGY training programs was investigated. The authors' study indicated that engaging and training PGY trainees through TED-style events could bridge the gap between acquired knowledge and professional competencies. Abstract: Objectives: Competency-based public communication skills are not systematically taught in most medical curricula, reflecting a gap between medical knowledge and holistic patient care as trainees transition into clinicians. We sought to investigate the efficacy of technology, entertainment, and design (TED) talks in postgraduate year (PGY) training programs. Methods: The authors organized an official internal TEDx event in which six PGY trainees volunteered as speakers. Two experienced physicians and two administrators also participated as speakers to provide trainees a didactic shadow learning experience. The remaining PGY trainees, along with clerks, physicians, nurses, pharmacists, and administrators, attended the conference. Before the event, speakers undertook individual training sessions and learned the principles of the presentation structure and storytelling mode. At the end of the event, a survey evaluating overall satisfaction in communication skills and professionalism was administered to all of the attendees. Results: Survey participants totaled 104, with a response rate of 97.2%. TEDx talks improved trainees' levels of patient care, communication, and professionalism. Speakers reported the high level of satisfaction with the event (mean 4.96 on a 5-point Likert scale; standard deviation 0.20). Participants agreed that the shadowing experience was useful and that the event encouraged them to pursue interests outside the medical field. Conclusions: This study highlights that TED is successful in terms of participant satisfaction and training in communication and professionalism. Engaging and training PGY trainees through TED-style events could bridge the gap between acquired knowledge and professional competencies. The authors recommend the implementation of TED-style events in medical training programs.